TO THE QUESTION OF DIAGNOSTIC STUDIES OF CHRONIC ALLERGIC RHINITIS IN WORKERS OF FIBERGLASS STRUCTURES PRODUCTION - M. T. Nasretdinova; Z. Kh. Karaboeva; N. A. Normuradov (European Science Publishing, 2024)
An open non-comparative clinical study was conducted to evaluate the effectiveness of the mineral-herbal remedy "DOLPHIN" for nasal irrigation in the treatment of allergic rhinitis among workers in the fiberglass construction manufacturing industry. The study involved 138 workers suffering from chronic allergic rhinitis. The results indicated a 72% reduction in nasal cavity complaints (itching, nasal congestion, discharge, sneezing) and a 64% reduction in eye complaints (itching, eye discharge) by the 30th day of using the remedy. Rhinoscopic data on the 30th day showed a 58% reduction in allergic rhinitis symptoms. The use of the "DOLPHIN" mineral-herbal remedy led to a 62% improvement in rhinocytogram data. The patients reported good tolerance (8.3 out of 10.0 points) and effectiveness (7.8 out of 10.0 points) of the remedy.
Keywords: allergic rhinitis,